O rizomie i cechach rizomatycznych na przykładzie powieści Michaiła Szyszkina „Взятие Измаила” - Nowak, Gabriela (Przegląd Wschodnioeuropejski, 2018)
The article is dedicated to the philosophical concept of rhizome developed by Gilles Deleuze and Felix Guattari. The author tries to define the capabilities and limitations of rhizome in becoming a methodology for the interpretation of texts. Analysis of the six rhizome principles: connection and heterogeneity, multiplicity, asignifying rupture, cartography and decalcomania, based on Mikhail Shishkin’s novel “The Taking of Izmail”, shows that only the rules of connection and heterogeneity and asignifying rupture seem to originate from European philosophical tradition. Therefore, only these three rules of rhizome may become a method of literary interpretation.